2020
DOI: 10.1038/s12276-020-00487-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between the microbiomes of tonsil and saliva samples isolated from pediatric patients subjected to tonsillectomy for the treatment of tonsillar hyperplasia

Abstract: Oral microbes have the capacity to spread throughout the gastrointestinal system and are strongly associated with multiple diseases. Given that tonsils are located between the oral cavity and the laryngopharynx at the gateway of the alimentary and respiratory tracts, tonsillar tissue may also be affected by microbiota from both the oral cavity (saliva) and the alimentary tract. Here, we analyzed the distribution and association of the microbial communities in the saliva and tonsils of Korean children subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…In relation to the specific bacterial species identified by culture in our samples, they are much in agreement with other studies performed either by culture or, more recently, by employing 16S rRNA gene sequencing ( Tables 2 , 3 ) ( 31 , 45 48 ). In our experiments, S. aureus (45%), H. influenzae (27%), N. subflava (23%) and S. Pyogenes (23%) were the most prevalent bacterial species in the core of hypertrophied tonsillar tissue within our cohort of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In relation to the specific bacterial species identified by culture in our samples, they are much in agreement with other studies performed either by culture or, more recently, by employing 16S rRNA gene sequencing ( Tables 2 , 3 ) ( 31 , 45 48 ). In our experiments, S. aureus (45%), H. influenzae (27%), N. subflava (23%) and S. Pyogenes (23%) were the most prevalent bacterial species in the core of hypertrophied tonsillar tissue within our cohort of patients.…”
Section: Discussionsupporting
confidence: 92%
“…Choi et al. ( 45 ) recently demonstrated that the microbiome profiles of saliva and tonsils are largely similar both, in terms of diversity and composition, in children operated due to OSA. Given the location of tonsils at the back of the oral cavity, it was somehow expected the close relation between the two microbial groups.…”
Section: Discussionmentioning
confidence: 99%
“…(Fagö-Olsen et al, 2019),(Choi et al, 2020),(Viciani et al, 2016),(Johnston et al, 2018),(Jeong et al, 2007). In our experiments, S. aureus (35%), H. influenzae (30%) and N. subflava (30%) were the most prevalent bacterial species in the core of hypertrophied tonsillar tissue within our cohort of patients.…”
mentioning
confidence: 50%
“…Interestingly, it has been shown that such process implies the most striking change in the salivary microbiome of all ages, when considering children from birth until 18 years old(Crielaard et al, 2011). Choi et al(Choi et al, 2020) recently demonstrated that the microbiome profiles of saliva and tonsils are largely similar both, in terms of diversity and composition, in children operated due to OSA. Given the location of tonsils at the back of the oral cavity, it was somehow expected the close relation between the two microbial groups.…”
mentioning
confidence: 99%
“…In contrast, culture-independent molecular pro ling based on 16S rRNA gene amplicon amplicon sequencing revealed only minor differences in the bacterial composition when different sampling sites in human tonsils and adenoids were compared [14]. Noteworthy, the majority of studies elaborating on the composition of the tonsillar microbiome have analyzed tissues from pediatric patients [14][15][16][17][18][19][20][21]. Tonsil cancer occurs only in adults and the few available datasets on the adult microbiome in tonsil cancer have not considered the inclusion of age-matched control cohorts [22,23].…”
Section: Introductionmentioning
confidence: 99%